Challenges of Data in Educational Planning - Oladiji, Alaba Adebola (NIU Journal of Humanities, 2018)
Premised on the haphazard way in which programmes are implemented in the educational sector which in most cases turned out that resources (human, materials and fund) were not adequate such that most programmes which could have optimally benefit the society turned out the negative way, this study examined the effect of data on planning. Planning is futuristic and can only be useful in as much as data is adequately available for appropriate planning. The study looks at planning and goes ahead to examine the place of data in planning. Various forms of data is brought into focus. The study also looked at challenges of data in education industry and goes ahead to suggest ways of alleviating challenges of data in education industry. The study suggested the use of modern Information Communication Technology in gattherin of data in education industry to minimize delays and distortion of data among other means. The study concluded by emphasizing that development and implementation of plans in education industry will always be a herculean task in the absence of appropriate data. Keywords: Data, Planning, Education Industry.